Antibacterial and anti‐inflammatory activity of a temporin B peptide analogue on an in vitro model of cystic fibrosis. (6th August 2014) - Bezzerri, Valentino; Avitabile, Concetta; Dechecchi, Maria Cristina; Lampronti, Ilaria; Borgatti, Monica; Montagner, Giulia; Cabrini, Giulio; Gambari, Roberto; Romanelli, Alessandra
<x xml:space="preserve">Abstract</x> Natural peptides with antimicrobial properties are deeply investigated as tools to fight bacteria resistant to common antibiotics. Small peptides, as those belonging to the temporin family, are very attractive because their activity can easily be tuned after small modification to their primary sequence. Structure‐activity studies previously reported by us allowed the identification of one peptide, analogue of temporin B, TB_KKG6A, showing, unlike temporin B, antimicrobial activity against both Gram‐positive and Gram‐negative bacteria. In this paper, we investigated the antimicrobial and anti‐inflammatory activity of the peptide TB_KKG6A against Pseudomonas aeruginosa. Interestingly, we found that the peptide exhibits antimicrobial activity at low concentrations, being able to downregulate the pro‐inflammatory chemokines and cytokines interleukin (IL)‐8, IL‐1β, IL‐6 and tumor necrosis factor‐α produced downstream infected human bronchial epithelial cells. Experiments were carried out also with temporin B, which was found to show pro‐inflammatory activity. Details on the interaction between TB_KKG6A and the P. aeruginosa LPS were obtained by circular dichroism and fluorescence studies. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.